Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
7(x-14)+35=25+279/9
7(x-14)+35=25+31
7(x-14)+35=56
7(x-14)=56-35
7(x-14)=21
x-14=21/7
x-14=3
x=3+14
x=17
[ 2 x X - 14 ] + 35 = 74
2 x X - 14 = 74 - 35
2 x X - 14 = 39
2 x X = 39 + 14
2 x X = 53
X = 53 : 2
X = 26 , 5
Vậy x = 26 , 5
(2xX-14)+35=74
2xX-14=74-36
2xX-14=38
2xX=38+14
2xX=52
x=52:2
x=26
a) \(x:\frac{2}{3}=150\)
\(x=150.\frac{2}{3}\)
\(x=100\)
b) \(\frac{35}{9}:x=\frac{35}{6}\)
\(x=\frac{35}{9}.\frac{6}{35}=\frac{2}{3}\)
c,d tương tự
a ) x : 2/3 = 150 c ) x : 4/7 = 180
x = 150 x 2/3 x = 180 x 4/7
x = 100 x = 720/7
b ) 35/9 : x = 35/6 d ) 49/8 : x = 49/5
x = 35/9 : 35/6 x = 49/8 : 49/5
x = 2/3 x = 5/8
{ ( 4 . x + 28 ) . 3 + 55 } = 35 . 5
{ ( 4 . x + 28 ) . 3 + 55 } = 175
{ ( 4 . x + 28 ) . 3 } = 175 - 55
{ ( 4 . x + 28 ) . 3 } = 120
{ ( 4 . x + 28 ) } = 120 : 3
4 . x + 28 = 40
4 . x = 40 - 28
4 . x = 12
x = 12 : 4
x = 3
Bài làm
245,68 - ( X : 4 + X 6 ) = 43,14 x 3
245,68 - ( X : 4 + X 6 ) = 129,42
(X \(\frac{1}{4}\) + X 6 ) = 245,68 - 129,42
X \(\frac{1}{4}\)+X 6 = 116,26
X x ( \(\frac{1}{4}\)+ 6 ) = 116,26
X x \(\left(\frac{1}{4}+\frac{24}{4}\right)\) = 116,26
X x \(\frac{25}{4}\)= 116,26
X x 6,25 = 116,26
X = 116,26 : 6,25
X = 18,6016
Vậy X = 18,6016
# Chúc bạn học tốt #